Acetic anhydride from acetic acid - Bulay, Alberto N. (College of Engineering, 1964)
Recommended process: Ketene process -- Raw materials: acetic acid, ammonia and triethyl phosphate -- Plant site: Rosario, Cavite and adjacent to Filoil Refinery -- Land area: 2,790 sq. m. -- Plant capacity: 24,000 pounds acetic anhydride per day for a 300 day year -- Fixed capital investment: 2,000,000.00 -- Percent Return on investment: before taxes at maximum sales: 20.9% -- Pay-out time: 3.24 years -- Break-even point: 42% of design capacity -- Shut-down point: 18% of design capacity -- Limitation: The proposed plant is not to be constructed until such a time when a great demand for acetic anhydride arises.